Factors Associated with the Incidence of Local Recurrences of Breast Cancer in Women Who Underwent Conservative Surgery - Juliana Rodrigues Tovar; Eliana Zandonade; Maria Helena Costa Amorim (International Journal of Breast Cancer)
Conservative surgery is considered the procedure of choice for women who are affected by early stage tumours. The local recurrence of cancer as a consequence of breast tissue conservation is a growing concern. This study aimed to describe the sociodemographic and clinical profiles of women who had local recurrences of breast cancer after conservative surgery and to examine the associations between sociodemographic and clinical variables and the incidence of tumour recurrence in these women. The retrospective cohort included 880 women who were diagnosed with breast cancer and underwent conservative surgery between January 2000 and December 2010. Recurrences occurred in 60 patients, and the mean age of the women at diagnosis was 48.8 years. Predictive factors for local recurrence were young age (<39 years) (P=0.028 and OR=10.93), surgical margin involvement (P=0.001 and OR=3.66), and Her-2 overexpression (P=0.045 and OR=1.94). The establishment of sociodemographic and clinical characteristics might help to select optimum treatments, which is a crucial challenge for public health in Brazil, especially with regard to reductions of surgery and hospitalisation expenditures in the Unified Health System (Sistema Único de Saúde—SUS).